KELAYAKAN MEDIA POSTER PERILAKU KONSUMSI BUAH MASYARAKAT KOTA PONTIANAK PADA SUBMATERI MENU SEHAT - Sintia, Mega; Candramila, Wolly; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe low frequency of fruit consumption of the people of Pontianak City should be anticipated through learning activities, for example through learning media by displaying the results of research on fruit consumption behavior in particular population. This study aimed to determine the feasibility of poster containing the result of study on the consumption behavior of the fruit in Pontianak City as a learning medium on Sub Material of Healthy Menu in second grade of high school. This was a descriptive study using questionnaire as non-test data collection technique. Medium validity was assessed by 2 lecturers in the Study Program of Biology Education and 3 high school biology teachers in Pontianak City. The validity test results were analyzed using the Lawshe’s Content Validity Ratio (CVR). The data analysis showed that the poster containing the Sub Material of Healthy Menu and the study of fruit consumption behavior of the people in Pontianak City was feasible to be used as a learning medium in Sub Material of Healthy Menu in second grade of high school based on the Lawshe’s CVR minimum value of 0.99 for 5 validators. Keywords: Feasibility, Healthy Menu, Poster